Finance, Islamic Finance: Theoretical Analysis - Zaman, Hasan (Australian Finance & Banking Review, 2020)
The paper discusses the steps to be taken to strengthen the efficiency and transparency of the Board and management. Increasing shareholders and depositors to play a more important role in protecting their own interests. The article then describes some of the popular resources available to enhance the effectiveness and responsibility of the Board and the Executive.